2020
DOI: 10.1093/cdn/nzaa111
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Supplementation during Suckling and Postweaning Periods Attenuates the Adverse Metabolic Effects of Maternal High-Fat Diet Consumption in Sprague-Dawley Rats

Abstract: Background Vitamin A (VA) is demonstrated to be a regulator of adipose tissue (AT) development in adult obese models. However, little is known about the effect of VA on obesity-associated developmental and metabolic conditions in early life. Objective To assess the effects of dietary VA supplementation during suckling and post-weaning periods on the adiposity and metabolic health of neonatal and weanling rats from mothers con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
3
7
1
Order By: Relevance
“…The changes may partially be the result of increased WAT in HFD pups and reduced tissue mass by the RA treatment. The findings on serum leptin are consistent with our previous study, in which maternal dietary VA supplementation was also found to decrease the enhanced serum leptin concentration in HFD pups (30) . Previous studies in adult rodent models also showed that chronic dietary VA supplementation reduced serum leptin as well as leptin gene expression in WAT (58,59) .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The changes may partially be the result of increased WAT in HFD pups and reduced tissue mass by the RA treatment. The findings on serum leptin are consistent with our previous study, in which maternal dietary VA supplementation was also found to decrease the enhanced serum leptin concentration in HFD pups (30) . Previous studies in adult rodent models also showed that chronic dietary VA supplementation reduced serum leptin as well as leptin gene expression in WAT (58,59) .…”
Section: Discussionsupporting
confidence: 92%
“…In adult rodents, RA was shown to inhibit adipogenesis and stimulate angiogenesis and apoptosis in white adipose tissue (WAT), and to increase the adaptive thermogenesis of brown adipose tissue (BAT) via regulating the expression of uncoupling proteins (UCPs) (26)(27)(28)(29) . Our previous study indicated that supplementing the maternal diet with VA during lactation significantly reduced the adiposity and modulated serum adipokines and lipids in neonatal and weanling rats from dams consuming a high fat diet (HFD) (30) . However, no study has evaluated the effect of direct RA administration on the AT development of neonates affected by maternal diet-induced obesity.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that any adverse outcomes of the in utero environment cannot be negated by the postweaning diet. Notably, supplementation of the diet with vitamin A in rats augmented metabolic dysfunction in offspring exposed to an obesogenic diet in utero (108). This suggests that some aspects of the postweaning diet may be beneficial in reducing the programming potential of a maternal obesogenic diet in pregnancy.…”
Section: Potential Interventions and Therapeuticsmentioning
confidence: 99%
“…Engulfment of apoptotic cells by macrophages leads to the synthesis of retinoids, which, in part, are responsible for some transcriptional changes of the M2-activation program and for the sustained phagocytosis capacity of macrophages [ 68 , 69 , 71 , 72 ]. Retinoids accumulate in the adipocytes and can inhibit adipocyte differentiation, reduce fat accumulation, and promote the expression of uncoupling protein 1 (UCP1) and the development of BAT-like adipocytes in WAT depots in mouse [ 73 , 74 , 75 , 76 , 77 ]. Expression of UCP1 confers BAT-like properties to WAT adipocytes, including thermogenic potential—a process termed adipocyte browning or beige adipogenesis [ 78 ].…”
Section: Metabolites Of Apoptotic Cells and Their Effect On Macrophagesmentioning
confidence: 99%